Temporary successful closed reduction of an atlantoaxial luxation in a horse - Licka, T.; Edinger, H. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
An eight year-old Welsh cob gelding (weighing 340 kg) was diagnosed with ventral luxation of the dens axis one day after trauma. Neurological signs included severe ataxia, wide stance and hypalgesia. Under general anaesthesia, closed reduction was achieved by maximum extension of the neck and subsequent manual impact on the ventral aspect of the transverse processes of the axis. A follow-up radiograph confirmed the reduction. Eight days later, re-luxation occurred, and as further attempts at nonsurgical and surgical reduction failed, the horse was euthanatised.
Keywords: Horse; vertebral luxation; reduction; neurology; atlanto-axial joint